INVESTIGAÇÃO DO EFEITO DA TEOBROMINA EM LINHAGEM DE MICRÓGLIAS HUMANAS BV-2 - Vielmo, Adriani Cheron (2022)
Neurodegenerative diseases are debilitating conditions that affect people of all ages and result from the progressive degeneration or death of neurons. Several pathological conditions such as Parkinson's disease, Alzheimer's disease, Huntington's disease, multiple sclerosis and stroke occur via oxidative stress and neuroinflammation, involving the formation of neurotoxic substances that further amplify the disease state. Neurodegenerative diseases have no cure, but there are treatments that aim to slow their progression and reduce symptoms. However, unfortunately, many therapies for the treatment of these neuronal diseases have side effects and consequently low adherence to treatment. In this scenario, it is extremely important that new investigations are carried out in order to identify new treatments with zero or reduced adverse effects. For many years, man has used natural substances, especially those of plant origin, in the treatment of various diseases. In this context, theobromine (TB) is inserted, which has numerous important biological properties, such as antioxidant and anti-inflammatory properties, being found in many functional products. Thus, the aim of this study was to evaluate the possible neuroprotective effect of theobromine on human microglia of the BV-2 lineage. To carry out the present investigation, BV-2 cells were plated in 96-well plates at a concentration of 2.5 × 10 5 cells/mL/well and treated with 1μg/mL of bacterial lipopolysaccharide (LPS) for 72 h to simulate a chronic neuroinflammation. Subsequently, the cells were treated with TB alone and associated with LPS at different concentrations (0.1; 0.5; 1; 5 and 10 μg/mL) for 24h. A control with the TB solvent, DMSO (0.001%), was also performed. After the incubation periods, assays were conducted to analyze the levels of cell proliferation and oxidative stress. The results found showed that both TB and DMSO did not show cytotoxicity, since they did not increase the levels of proliferation and oxidative stress, TB was still able to reduce baseline levels of nitric oxide. However, LPS increased cell proliferation and oxidative stress by increasing the production of reactive oxygen species (ROS) and superoxide. When cells were treated with LPS and TB, there was a decrease in proliferation levels and a reduction in ROS production, only at the intermediate concentration of TB (1μg/ml), compared to the LPS control. Thus, the set of results found in the present study suggested that TB had a neuroprotective action via modulation of the levels of cell proliferation and oxidative stress. Therefore, these findings point to TB as a potential neuroprotective agent, with an excellent profile to be used in new therapies for neurodegenerative diseases.